Pharmacokinetics of Esomeprazole in Critically Ill Patients - Xu, Yanyan; Tian, Xin; Wang, Wei; Tian, Weiqiang; Zhang, Tao; Sun, Jian; Zhou, Qingyun; Shao, Chuxiao (Frontiers in Medicine, 2022)
Background Esomeprazole, a potent proton pump inhibitor (PPI), is widely used for the prevention of stress ulcers in intensive care unit (ICU) patients. Objective This study investigates the pharmacokinetics (PK) of esomeprazole in critically ill patients. Methods The study included eligible adult ICU patients who received endotracheal intubation assisted mechanical ventilation for more than 48 h and had at least an extra risk factor for stress ulcers. All enrolled patients received once-daily intravenous (IV) esomeprazole 40 mg. After the first dose of esomeprazole was administrated, serial blood samples were collected at 3, 5, 15, 30 min and 1, 2, 4, 6, 8, and 10 h. The total sample concentrations of esomeprazole were measured by UPLC-MS/MS. Esomeprazole PK parameters were analyzed using noncompartmental analysis. Results A total of 30 patients were evaluable. Mean age and body mass index (BMI) were 61.97 years and 23.14. PK sampling on the first dose resulted in the following median (IQR) parameters: AUC0−∞ 8.06 (6.65–9.47) mg·h/L; MRT0−∞ 4.70 (3.89–5.51) h; t1/2 3.29 (2.7–3.87) h; V 24.89 (22.09–27.69) L; CL 6.13 (5.01–7.26) L/h; and Cmax 2.56 (2.30–2.82) mg/L. Conclusions According to the label of esomeprazole, our study showed different esomeprazole PK parameters in ICU patients compared with healthy volunteers. Esomeprazole has unique pharmacokinetic parameters in critically ill patients.